Genetic determinants and postorthodontic external apical root resorption in Czech children - Borilova Linhartova, P; Cernochova, P; Kastovsky, J; Vrankova, Z; Sirotkova, M; Izakovicova Holla, L (Oral diseases, 2017)
Objective Genes, involved in the modulation of inflammatory response and bone remodeling, play a role in the development of postorthodontic external apical root resorption (EARR). The aim of our study was to analyze possible associations between seven single nucleotide polymorphisms (SNPs) in interleukin‐17A (IL‐17), osteopontin (SPP1), purinoreceptor P2X7 (P2RX7), and tumor necrosis factor receptor superfamily member 11B (TNFRSF11B) genes and EARR in children after orthodontic treatment. Subjects and Methods This case–control study comprised 99 orthodontically treated patients (69 controls and 30 subjects with EARR). Genotype determinations of rs2275913, rs11730582, rs9138, rs208294, rs1718119, rs3102735, and rs2073618 were based on polymerase chain reaction using 5′ nuclease TaqMan® assays. Results While no significant differences were observed in allele or genotype frequencies of all seven studied SNPs, specific haplotype of P2RX7 (rs208294 and rs1718119) modified the risk of EARR development (P < 0.05). In addition, the length of treatment with a fixed orthodontic appliance positively correlated with the presence of EARR (P < 0.05). Conclusions Although the effect of individual SNPs studied on the EARR development was not confirmed in the Czech population, complex analysis suggested that variability in the P2RX7 gene and the length of orthodontic treatment may be important factors contributing to the etiopathogenesis of postorthodontic EARR.